Repeated cross-sectional surveys show a decreasing trend in Borrelia burgdorferi sensu lato seroprevalence over a 50-year period, Finland, 1966 to 2017 - Lamppu, Maija; Klemola, Tero; Vesterinen, Eero; Dub, Timothée; Pietikäinen, Annukka; Hytönen, Jukka (European Centre for Disease Control and Prevention (ECDC), 2026)
BACKGROUND
Lyme borreliosis (LB) caused by Borrelia burgdorferi sensu lato (Bbsl) spirochetes is the most common tick-borne infection in Europe and the incidence of LB has been increasing in many countries.AIMWe examined changes in Bbsl seroprevalence in Finland over the past 50 years.
METHODS
We analysed samples collected from people aged ≥ 15 years in nationwide cross-sectional health surveys conducted over the years 1966-1972, 1978-1980, 2000-2001 and 2017. Samples were screened with an IgG ELISA assay and confirmed with an IgG bead immunoassay. We assessed factors associated with Bbsl seropositivity by generalised linear models.
RESULTS
Seroprevalence was highest in 1966-1972 (25.0%; 95% confidence interval (CI): 22.3-27.7%), while it was lower in 1978-1980 (16.6%; 95% CI: 14.3-18.9%), 2000-2001 (7.4%; 95% CI: 5.8-9.0%) and 2017 (3.4%; 95% CI: 2.3-4.5%). Male sex (p = 0.0014) and increasing age (p < 0.0001) were associated with higher seropositivity. The estimated probability of being seropositive was highest among residents from southern (least squares (LS) mean: 0.164; 95% CI: 0.139-0.192), central and eastern Finland (LS mean: 0.141; 95% CI: 0.116-0.170) and lowest in northern Finland (LS mean: 0.019; 95% CI: 0.014-0.028).
CONCLUSION
Our results show a decrease in the seroprevalence in Finnish people over time. Reasons for this decrease are not clear but could be related to urbanisation, increased awareness, effective diagnostics and prompt antibiotic treatments. Overall, this study demonstrates how repeated serosurveys can help in revealing trends and identifying potential risk groups.